2008
DOI: 10.4028/www.scientific.net/msf.595-598.251
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Evolution of Slurry Fe Aluminide Coatings during High Temperature Steam Oxidation

Abstract: Slurry iron aluminide coatings are very resistant to steam oxidation at 600-650º C. These coatings can be used to protect new generation Ultra Super Critical (USC) steam power plant ferritic/martensitic steel components. The microstructure of the initially deposited coating changes as a function of time, mainly due to coating-substrate interdiffusion, going from mostly Fe2Al5 to FeAl, causing the precipitation of AlN in those substrates containing a minimum content of N and moreover, developing Kirkendall poro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 17 publications
3
17
0
Order By: Relevance
“…There is no evidence of substrate attack through cracks likely due to the fact that there is sufficient Al within this zone, allowing to form a protective Al oxide. This was confirmed by earlier investigations, which showed that a protective Al oxide developed on the cracks surface, eventually filling it [17]. The longer exposed specimens (Fig.…”
Section: Slurry Iron Aluminide Coatingsupporting
confidence: 77%
See 4 more Smart Citations
“…There is no evidence of substrate attack through cracks likely due to the fact that there is sufficient Al within this zone, allowing to form a protective Al oxide. This was confirmed by earlier investigations, which showed that a protective Al oxide developed on the cracks surface, eventually filling it [17]. The longer exposed specimens (Fig.…”
Section: Slurry Iron Aluminide Coatingsupporting
confidence: 77%
“…8a [12,17]. The coating exhibits through thickness cracks likely formed by mismatch between the thermal expansion coefficients of the different phases.…”
Section: Slurry Iron Aluminide Coatingmentioning
confidence: 99%
See 3 more Smart Citations